Populasi dan Spesies Serangga Hama di Gudang dengan Penciri Lantai dan Pintu yang Berbeda di Tiga Pasar Lokal di Kecamatan Kemuning dan Sako, Kota Palembang Sumatera Selatan - Asti, Meirin; Herlinda, Siti; Yulistin, Eka; Setyawati, Anita; Anggraini, Erise; Rahmawati, Aulya; Nandyta, Alifya Nesya; Salsabilla Sirega, Septiana Rezeki; Nabiha Putra, Naka Rashad; Panjaitan, Hendrik Haposan (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Asti, M., Herlinda, S., Yulistin, E., Setyawati, A., Anggraini, E., Rahmawati, A., Nandyta, A. N., Siregar, S. R. S., Putra, N. R. N., & Panjaitan, H. H. (2024). Population and Storage Pest Species from Three Local Markets with Various Floors and Doors in Sub-district of Kemuning and Sako, Palembang South Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 143–155). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Storage pests caused considerable harm in storage facilities due to their quick reproductive capacity, ease of dissemination, and facilitation of mold proliferation. This research aimed to identify insect species present in storage commodities through the observation and morphological identification of warehouse pest species. The research was performed via a microscope and identification manuals, with specimens gathered from the distribution of warehouse insects in the markets of Palembang City. Data acquired using sample techniques and specification determination. Observations conducted in various marketplaces within the Palembang region revealed that the warehouse pest population table indicated distinct population variability for each species across the markets. The species comprise Sitophilus oryzae, Tribolium castaneum, Oryzaephilus surinamensis, Cryptolestes ferrugineus, Carpophilus dimidiatus, and Rhyzopertha dominica. Each species possesses distinct traits, whether in the head, thorax, or abdomen. The species Tribolium castaneum was only located in the Kebun Semai market, whereas the population of Oryzaephilus surinamensis was predominantly discovered in the Perumnas market. The species Rhyzopertha dominica and Cryptolestes ferrigineus were predominantly found at the Sekip Ujung Market and Kebun Semai Market. In the Perumnas market, there are 22 specimens of S. oryzae and 18 specimens of O. surinamensis. In the Sekip Ujung market, there are 18 specimens of R. dominica and 19 specimens of S. oryzae. In the Kebun Semai market, there are 17 specimens of R. dominica, 13 specimens of T. castaneum, and 11 specimens of C. ferrugineus, respectively. The state of the warehouse's physical condition. The implementation of ceramic floors, net-covered open ventilation, roll-up doors, pallets, and a zinc roof helps mitigate insect populations in the storage warehouse, hence minimizing damage to commodities.